2020
DOI: 10.5194/gmd-2020-218
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Comparative Study of Two-way and Offline Coupled WRF v3.4 and CMAQ v5.0.2 over the Contiguous U.S.: Performance Evaluation and Impacts of Chemistry-Meteorology Feedbacks on Air Quality

Abstract: Abstract. The two-way coupled Weather Research and Forecasting and Community Multiscale Air Quality (WRF-CMAQ) model has been developed to more realistically represent the atmosphere by accounting for complex chemistry-meteorology feedbacks. In this study, we present a comparative analysis of two-way (with consideration of both aerosol direct and indirect effects) and offline coupled WRF v3.4 and CMAQ v5.0.2 over the contiguous U.S. Long-term (five-year of 2008–2012) simulations using WRF-CMAQ with both offlin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 86 publications
(143 reference statements)
0
2
0
Order By: Relevance
“…(2015) and Wang et al. (2020) described similar warm biases in their long‐term WRF‐CMAQ simulations, which Wang et al. attribute to deeper PBL heights related to the ACM2 PBL scheme in WRF and to the use of the soil moisture nudging technique used in the PX land surface model scheme in WRF.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…(2015) and Wang et al. (2020) described similar warm biases in their long‐term WRF‐CMAQ simulations, which Wang et al. attribute to deeper PBL heights related to the ACM2 PBL scheme in WRF and to the use of the soil moisture nudging technique used in the PX land surface model scheme in WRF.…”
Section: Resultsmentioning
confidence: 72%
“…Model biases ( Figure S2 in Supporting Information S1 ) show comparable behavior. Hogrefe et al (2015) and Wang et al (2020) described similar warm biases in their long-term WRF-CMAQ simulations, which Wang et al attribute to deeper PBL heights related to the ACM2 PBL scheme in WRF and to the use of the soil moisture nudging technique used in the PX land surface model scheme in WRF. A comparison between the 1.33-km modeled PBL heights and PBL measurements made at Queens College and at CCNY between June 27 and July 12 ( Figure S1 in Supporting Information S1 ) revealed that all simulations produced deeper daytime PBL heights compared to observations.…”
Section: Resultsmentioning
confidence: 73%